Lifelong learning at its best innovative practices in adult credit programs - Maehl, William H. 1930- (Jossey-Bass higher and adult education series, 1999)
"Drawing from data gathered by the Commission for a Nation of Lifelong Learners - in a study directed by a prestigious panel of educational and business leaders - William Maehl details educational strategies that have been most successful with adult learners across the nation. Using examples from settings as diverse as Georgetown University and Toyota, Maehl describes a wide range of winning program models that illustrate the goals of lifelong learning in practice. Organized under such key learning objectives as competence, collaboration, and self-directedness, these success stories reveal the specific instructional, organizational, financial, and other program components that make the greatest difference in learning outcomes."--Jacket.